Factors Influencing Green Purchasing Inconsistency of Ecuadorian Millennials - Carrión Bósquez, Nelson Geovany (Pontificia Universidad Católica del Perú, 2021)
Environmental protection has become one of the main concerns for consumers, which is why green consumption is an alternative to balance customer demand satisfaction and environmental protection. Despite the existence of different studies on green consumption, several questions remain unanswered, one of them is ¿why environmental awareness does not always lead to real purchases? which shows a need to know the factors that influence this behavior gap. This research aimed to identify whether attitudes and subjective norms influence the green purchase intentions of Ecuadorian millennials, it also analyzed whether the purchase intentions resulted in actual purchases, as well as the factors that influenced green purchasing inconsistencies. The research was quantitative and cross-sectional design, 710 millennials participated in the study. The questionnaire consisted of 26 questions and the data obtained were subjected to Cronbach's Alpha tests and Exploratory Factor Analysis. Finally, the validity of the proposed model was verified through a Confirmatory Factor Analysis and Structural Equations, using IBM SPSS Statistics 2.0. and AMOS 24. The results showed that subjective attitudes and norms influence purchase intentions. However, 82% of those intentions did not result in actual purchases. Habits are the main factor influencing green inconsistencies, while skepticism influences purchase intentions, availability and lack of knowledge influences consumer habits.

La protección ambiental es en una de las principales preocupaciones de los consumidores, permitiendo que el consumo verde equilibre la satisfacción de la demanda del cliente y la protección ambiental. A pesar de existir varios estudios sobre el consumo verde, varias preguntas siguen sin responderse, uno de ellas es ¿por qué la conciencia medioambiental no siempre conduce a compras reales? mostrando la necesidad de conocer los factores influyentes en esta brecha de comportamiento. El estudio identificó la influencia de las actitudes y las normas subjetivas en las intenciones de compra verde de los millennials ecuatorianos, también analizó si las intenciones de compra concluyeron en compras reales y los factores influyentes en las inconsistencias de compra. La investigación fue cuantitativa y transversal, 710 millennials participaron en el estudio. El cuestionario tuvo 26 preguntas y los datos fueron sometidos a pruebas Alfa de Cronbach y un Análisis Factorial Exploratorio. Finalmente, se verificó la validez del modelo propuesto a través de un Análisis Factorial Confirmatorio y Ecuaciones Estructurales, usando IBM SPSS Statistics 2.0. y AMOS 24. Los resultados mostraron que las actitudes y las normas subjetivas influyen en las intenciones de compra. Sin embargo, el 82% de esas intenciones no resultaron en compras reales. Los hábitos son el principal factor que influye en las inconsistencias de compra verde, mientras que el escepticismo influye en las intenciones de compra, la disponibilidad y falta de conocimiento influye en los hábitos de consumo.
Keywords: Medio ambiente; Jóvenes consumidores--Ecuador; Comportamiento del consumidor; Impacto ambiental; https://purl.org/pe-repo/ocde/ford#5.02.04